Rapid Genotyping of β-tubulin Polymorphisms in Trichuris trichiura and Ascaris lumbricoides. - Nour Rashwan; Marilyn Scott; Roger Prichard (Public Library of Science (PLoS), 2017)
BACKGROUND:The benzimidazole (BZ) anthelmintics, albendazole (ABZ) and mebendazole (MBZ) are the most common drugs used for treatment of soil-transmitted helminths (STHs). Their intensive use increases the possibility that BZ resistance may develop. In veterinary nematodes, BZ resistance is caused by a single nucleotide polymorphism (SNP) in the β-tubulin isotype 1 gene at codon position 200, 167 or 198, and these SNPs have also been correlated with poor response of human Trichuris trichiura to BZ treatment. It is important to be able to investigate the presence of resistance-associated SNPs in STHs before resistance becomes clinically established. METHODS:The objective of this study was to develop new genotyping assays to screen for the presence of β-tubulin SNPs in T. trichiura and Ascaris lumbricoides. Rapid, simple and accurate genotyping assays were developed based on the SmartAmp2 method. Primer sets were optimized and selected to distinguish the SNP-variant genotypes. After initial optimization on control plasmids, the feasibility of the assay was assessed in field samples from Haiti and Panama. Finally, spiked fecal samples were assessed to determine the tolerance of Aac polymerase to fecal inhibitors. FINDINGS:Rapid SNP genotyping assays were developed to target β-tubulin polymorphisms in T. trichiura and A. lumbricoides. The assays showed high sensitivity and specificity in field samples and also demonstrated high tolerance to PCR inhibitors in fecal samples. CONCLUSION:These assays proved to be robust and efficient with the potential to be used as field tools for monitoring SNPs that could be associated with BZ resistance. However, further work is needed to validate the assays on large numbers of field samples before and after treatment.